Fuzzy logic application in the evaluation of performance of a prototype vehicle powered from solar energy and water electrolysis process - dos Santos, Marcos; Bahiana, Bruna Russo; Reis, Marcone Freitas dos; Martins, Ernesto Rademaker; Dias, FabrÃcio da Costa (International Journal of Applied Mathematical Research, 2016)
The purpose of this paper is to evaluate the performance of a prototype vehicle that uses a reversible fuel cell capable of producing and storing hydrogen and oxygen by breaking the water molecule - the electrolysis process, made possible with the use of solar panels. The vehicle shown only uses two main sources of energy: solar and hydrogen cells, both clean and renewable energy sources. Water is the only residue generated. The Fuzzy Logic was used in the establishment of linguistic variables and on the composition of inference rules based on power, solar panel area and solar irradiation. The Fuzzy Logic provides a method of translating verbal, vague, imprecise and qualitative expressions, common in human communication in numeric values. This enables the conversion of the human experience in a way understandable by computers. Thus, the technology made possible by the fuzzy approach has a practical value. In view of the severe environmental degradation in which the planet is going through and the scarcity of energy sources, especially fossil fuels, one of the great challenges of the scientific community is to develop new technologies that use clean and renewable energy sources, that are economically viable and promote sustainable technologies and processes.